Cytotoxic and anti-tumour properties of certain taxa of Umbelliferae with special reference to Centella asiatica (L.)Urban - Babu, T.D.; Kuttan, G.; Padikkala, J.
Centella asiatica (L.)Urban (Umbelliferae)is commonly used in the Ayurvedic system of medicine to treat various diseases. The present study examines the anti-tumour effect of the crude extract (CE)of Centella asiatica as well as its partially purified fractions (AF)from chromatographic procedures by both in vitro short and long term chemosensitivity and in vivo tumour model test systems. AF dose dependently inhibited the proliferation of the transformed cell lines significantly more than did the CE and other solvent fractions. Fifty percent effective doses on hour 3 exposure to AF were 17 and 22 #g/ml for Ehrlich ascites tumour cells (EAC)and Dalton's lymphoma ascites tumour cells (DLA), respectively. However, practically no toxic effects were detected in normal human lymphocytes. AF also significantly suppressed the multiplication of mouse lung fibroblast (L-929)cells at a concentration of 8 t~g/ml in long term culture. Oral administration of the extracts (CE and AF)retarded the development of solid and ascites tumours and increased the life span of these tumour bearing mice. Tritiated thymidine, uridine and leucine incorporation assay suggest that the fraction acts directly on DNA synthesis.
Keywords: CENTELLA ASIATICA; UMBELLIFERAE; CYTOTOXICITY; ANTI-TUMOUR